DEBT CHARACTERISTICS IN FINANCING BASED ON PROFIT SHARING PRINCIPLES IN SHARIA BANKS - Usanti, Trisadini Prasastinah; Nurwahjuni, Nurwahjuni; Setiawati, Anindya Prastiwi; Setiawati, Nur Utari (Srawung: Journal of Social Sciences and Humanities, 2025)
One of the fundamental principles underlying financing in sharia banks is the principle of profit sharing, specifically in mudharabah and musyarakah contracts. These financing schemes are characterized by the sharing of business profits and losses. However, the term “debt” appears in the clauses of mudharabah and musyarakah financing contracts in sharia banks and in several Religious Court decisions. In fact, financing based on the profit-sharing principle constitutes a partnership between capital and labor, not a debt or credit contract. Therefore, in mudharabah financing, if a loss occurs that is not due to the negligence of the capital manager (mudharib), it is borne by the capital owner (shahibul maal), whereas in musyarakah financing, losses are borne jointly. This study examines the issue of debt in financing based on the profit-sharing principle. The approaches employed include statutory, conceptual, and case law analysis. The term “debt” in this context refers to an outstanding obligation in the form of financing capital and the profit-sharing portion derived from the ongoing business income of the mudharib, which is the rightful share of the shahibul maal. However, the profit-sharing portion from a business that has ceased operations is not considered a debt that the mudharib is obligated to repay to the shahibul maal.